Synthesis of 14H-dibenzoxanthenes in green media using Sn(II)/nano silica as an efficient catalyst - Tavakol, Hossein; Firouzi, Mahdieh (Frontiers in Chemistry, 2022)
In this project, Sn(II)/nano silica has been prepared using a simple deposition of SnCl2.2.H2O on nano silica. The prepared catalyst has been used as a green and reusable catalyst for the synthesis of 14H-dibenzoxanthenes through one-pot condensation reaction of β-naphthol with various aliphatic and aromatic aldehydes. Several xanthene derivatives have been synthesized using ethanol as solvent, 10 mol percent of the catalyst, at reflux condition, in average 3 hours, and by 48-94% yield. Structure of synthesized derivatives confirmed by melting point, FT-IR, 13C-NMR, 1H-NMR analysis. Additionally, nanocatalyst composition confirmed by SEM, EDX, FT-IR and XRD analysis.